Can anyone stop the illegal sale of medicines online?. (7th March 2016) - Jack, Andrew; ,
Abstract : Demand for and supply of unlicensed drugs online continues to grow despite regulators' constant attempts to crack down on illegal activity, Andrew Jack reports